Stress Management Coping Strategies of Academic Leaders in an Institution of Higher Learning in Malaysia - Gurnam Kaur Sidhu; Nor Sa'adah Aziz (UiTM Publisher, 2015)
In today's demanding academic environment, academic leaders need to be well equipped with stress management coping strategies as they often find themselves in challenging situations and responsibilities. Therefore, the main aim of this paper is to investigate the stress management coping strategies used by academic leaders in an institution of higher learning located in Selangor, Malaysia. A mixed-methods research design was employed and the sample population involved 46 academic leaders from a public university. Data were collected using a questionnaire and semistructured interviews. The quantitative data were statistically analyzed using SPSS while the qualitative data were analyzed thematically. The findings showed that a majority of the academic leaders opted towards positive problem-focused engagement strategies such as cognitive restructuring and problem solving strategies followed by emotion-focused engagement which included expressing emotion and social support strategies. Besides that, academic leaders did confess that they sometimes do use disengagement strategies such as wishful thinking, problem avoidance and self-criticism coping strategies but they stressed that they faced problems and stress in a positive and constructive manner. The findings of this study imply that academic leaders in this study are engaged and well informed of stress coping strategies. However, it is recommended that top management in institutions of higher learning take the initiatives in providing necessary support to academic leaders by educating them on stress management coping strategies.